#TITLE_ALTERNATIVE# - M. FRIDHO FINANTHEO (NIM : 15109079) ; Pembimbing (1) : Dr. Heri Andreas, ST., MT. ; Pembimbing (2
Pantai Mutiara is a reclamated residential area on the northern Jakarta coastal area that is being affected by the land subsidence phenomenon. One of the causes of the phenomenon is the inability of the reclamated area to withstand the load of the buildings and infrastructure. The land subsidence that occurs on the area makes the area lower than the sea level thus causing the sea water to inundate the region. This phenomenon is called the flood inundation of sea water. The land subsidence and the flood inundation of sea water causes negative effects such as building damages that brings severe asset losses. The loss of assets needs to be estimated to help minimize the losses. One of the methods to calculate the potential losses due to the land subsidence and flood inundation of sea water is by using the Terrestrial Laser Scanner (TLS). The utilization of the TLS is used to model the Pantai Mutiara region in 3D. The phases in the TLS data processing includes the registration, georeferencing, filtering, meshing, digitation of the buildings and the region ground surface framework, and also to create the buildings and ground model surface. The potential of the asset losses can be estimetad by using the 3D model informations, the area data of the ground surface and buildings and also the price data of the land and buildings per m2 that is obtained based on the NJOP prices and the market prices of the Pantai Mutiara region. The results shows that the potential of asset losses of the Pantai Mutiara region has a 1,34 trillion rupiah value by using the NJOP price and 5,5 trillion rupiah by using the market pric